Stereotactic Radiotherapy for Localized External Auditory Canal Carcinomas: Report of Four Cases - Mori, Yoshimasa (Cureus, 2021)
External auditory canal carcinoma (EACC) is sometimes diagnosed at an early stage because it arises superficially in the ear canal and may cause ear obstruction symptoms early. In addition, in the early stage of EACCs, involvement of lymph nodes or distant metastases are reported less frequently. And so, stereotactic radiotherapy (SRT) concentrating high-dose radiation on the primary tumor may be an effective option. The aim of this study is to evaluate the preliminary results of upfront SRT for early-stage localized EACCs. Four cases (four females, 84 to 98 years old) with EACC of N0M0 (=no lymph node involvement and no distant metastasis) were treated. All four tumors (0.30 - 11.1 ml in volume) were diagnosed as squamous cell carcinoma histologically. A total dose of 24 - 33 Gy in 3 - 5 fractions (D95 [dose delivered to 95% of the target volume]=100% dose) was delivered by SRT using CyberKnife. All four cases were alive at the end of the follow-up period of 19 to 106 months. In three cases (tumor volume, 0.3 - 3.5 ml) the treated tumors had regressed or disappeared by the end of the follow-up period of 106, 28, and 19 months respectively. In the remaining one case, the treated tumor (11.1 ml) regrew and cervical lymph node metastasis occurred, and both were treated with SRT again 6 months and 20 months after the initial SRT respectively. The tumors were still stable at 39 months after the initial SRT. In conclusion, in three cases the small tumors had regressed or disappeared without lymph node involvement or distant metastasis. In the remaining case, additional SRT was performed for recurrent tumors, after which the patient’s condition remained stable. SRT may be an effective option for early-stage EACCs.